Cultural Identity in Contemporary Turkish Architecture Case Study in Konya - Fatih Canan; Selçuk Sayın; Mustafa Korumaz (Iconarp International Journal of Architecture and Planning, 2015)
Today in many countries, new solutions and trends in architecture field to express cultural identity against the pressure of internationalism appear in different qualitative values. In the example of Turkey, even today, if the problem of the identity affirmation in architecture continues, in fact, the historical origin of this problem coincides with the last period of the Ottoman Empire and early Republican period. Since the 20s to today, we can see the efforts to reflect national and modern identity in architectural designs, especially in public buildings.. In this study, firstly, the relationship between architecture and identity will be examined. Then after, buildings reflecting identity trends designed by famous architects such as Sedat Hakkı Eldem and Turgut Cansever from different periods in Turkey will be presented. The current architectural achievements in the generality of our country will be reviewed by a critical perspective. The city of Konya will be chosen for the special study areas. These buildings are banks, administrative and culture buildings. Trend analysis of identities in the current architectural achievements will be realized taking into account the following criteria: the metaphor, interpretation - synthesis and direct imitation. The architectural elements belonging to the Seljuk Empire that Konya was the capital between 11 th and 13 th century, will be frequently present in the selected samples. In conclusion, the defended ideas will be the following: New products of art and architecture should always be designed with an original and innovative approach. The use of direct imitation in new architectural achievements to establishing a link with the past does not always positive effect on architectural quality. The historic architectural elements used in order to create an identity in modern architecture should be interpreted with caution.